Biodiversity and National Protected Areas in Environmental Impact Assessment: Advances and Pending Issues - Aldana Durán, Martha Inés (2022)
This article analyzes biodiversity within the environmental impact assessment process, with special emphasis on its application in Protected Areas (PA). Additionally, it introduces the applicable international standards on the subject and reviews the applicable Peruvian national regulations. A sample of evaluation reports done by the National Service of Natural Protected Areas (SERNANP) which is the governing authority in the field of PA, is presented in order to identify the existing regulatory needs in this matter with a view to proposing the development of required objective criteria.